Deletion of alpB Gene Influences Outer Membrane Vesicles Biogenesis of Lysobacter sp. XL1 - Kudryakova, Irina V.; Afoshin, Alexey S.; Ivashina, Tanya V.; Suzina, Natalia E.; Leontyevskaya, Elena A.; Leontyevskaya (Vasilyeva), Natalia V. (Frontiers in Microbiology, 2021)
Outer membrane vesicles (OMVs) produced by Gram-negative bacteria constitute important factors in defining interactions with the extracellular milieu. Lysobacter sp. XL1 produces OMVs capable of lysing microbial cells, due to the presence in their cargo of bacteriolytic protease L5 (AlpB). Although protein L5 has been functionally and biochemically characterized (including aspects of its packing into OMVs), its role in vesicles biogenesis through genetic deletion of alpB had not been studied previously. Here, we have successfully deleted alpB by allelic replacement, and shown that the alpB deletion mutant produces a significantly lower amount of OMVs that lack bacteriolytic activity and display altered ultrastructural characteristics in relation to the OMVs produced by the wild-type strain. These results confirm that, as previously proposed, protein L5 participates in OMV production through a mechanism that is not yet fully understood.